Pengaruh Perbandingan Sosial terhadap Citra Tubuh pada Remaja Akhir Putri Pengguna Instagram - Marlinda, Devi; Sutatminingsih, Raras; Daulay, Debby Anggraini (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2022)
Late adolescents have a high interest in establishing relationships with the opposite sex along with a great desire to be accepted by the surrounding environment. This encourages late teens to focus on the concept of the ideal body, especially women. The concept of the ideal body is closely related to body image. One of the factors that influences body image is social comparison. This research aims to find out whether there is an influence of social comparison on body image. This research used an incidental sampling technique and involved 384 respondents who were late teenage girls who used Instagram, aged 18-21 years. Data collection used three scales, namely the body image scale and the social comparison scale. The analysis technique used in this research is simple linear regression analysis. The research results show that there is an influence of social comparison on body image in late adolescent girls who use Instagram (0.000ρ < .05).